Sthenelais Kinberg 1856 - Barnich, Ruth; Haaren, Ton Van (Zenodo, 2021)
Genus Sthenelais Kinberg, 1856 (emended) Sthenelais Kinberg, 1856: 387 (type species Sthenelais helenae Kinberg, 1856; revised by Pettibone 1971). Conconia Schmarda, 1861: 150 (type species Conconia caerulea Schmarda, 1861 = Sthenelais helenae Kinberg, 1856). Diagnosis BODY. Elongate, with numerous segments; mid-dorsum bordered by few pairs of small ctenidia. ELYTRA. Numerous, on segments 2, 4, 5, 7, continuing on alternate segments to 27, then on every segment to end of body. Dorsal tubercles on segments 3, 6, 8, continuing on alternate segments to 26. PROSTOMIUM. Rounded, fused to first segment. Median antenna inserted terminally, with stout, cylindrical ceratophore with lateral auricles and tapering style. Lateral antennae fused to inner dorsal sides of tentaculophores, without ceratophore, distinctly shorter than dorsal tentacular cirri. Paired palps encircled by palpal sheath emerging ventrally to tentaculophores. TENTACULOPHORES. With single aciculum, a pair of tentacular cirri, two bundles of capillary chaetae, L-shaped inner tentacular lobe with ciliated ridge and fused to palpal sheath, and dorsal tentacular crest. SEGMENT 2. With first pair of elytra, biramous parapodia and buccal cirri longer than following ventral cirri. Small ctenidia on lateral lips and medial to ventral cirri in anterior segments. SEGMENT 3. With dorsal tubercles fused to posterior sides of elytrophores of segment 2. Dorsal cirri absent. BRANCHIAE. Cirriform, absent in anteriormost segments. DORSAL CIRRI. Absent from all segments. VENTRAL CIRRI. Styles with or without basal knob and without long basal papillae. PARAPODIA. Biramous, each with up to three cup-shaped ctenidia dorsal to notopodia, noto- and neuropodial acicular lobes with accessory bracts and smooth stylodes on most parapodia (minute papillae may be present on stylodes in juveniles or in anteriormost parapodia of adults). Notopodial acicular lobes nearly completely encircled by a bract covering the basis of the notochaetae. Neuropodial acicular lobes posteriorly with a large bilobed bract and anteriorly with two smaller crescent-shaped bracts. CHAETAE. Notochaetae slender, spinous, tapering to capillary, uni- or bidentate tip. Neurochaetae usually compound falcigers and, if present, few compound spinigers and/or simple spinous chaetae; stems of compound chaetae usually with few rows of spines distally. Neurochaetae arranged in three groups: upper group of neurochaetae within anterodorsal bract: mainly slender compound falcigers; few simple, spinous chaetae (may be missing); in some species also few compound spinigers. Middle group of neurochaetae within posterior bract: all stout compound falcigers. Lower group of neurochaetae within anteroventral bract: all slender compound falcigers. Remarks The generic diagnosis of Sthenelais is emended for the potential presence of minute papillae on the stylodes found in juveniles or in anteriormost parapodia of adult S. boa and for the presence of compound spinigers found in S. limicola (see below). Wehe (2007) was the first to mention that the capillary notochaetae of S. boa taper to a bidentate or unidentate tip and emended the generic diagnosis of Sthenelais accordingly. We confirm the presence of bidentate and unidentate (i.e., simple) tips for the capillary notochaetae of S. boa , while those of S. limicola are all simple, see below. Based on our study, Sthenelais currently comprises two valid species in the wider Northeast Atlantic: Sthenelais limicola (Ehlers, 1864), which is the most widespread and common nearshore and offshore, and Sthenelais boa (Johnston, 1833), which is found usually nearshore. For an extensive list of synonyms, or species previously referred to Sthenelais , which belong to other genera, or species that require further investigation, see Table 2 and the respective paragraphs below. : Published as part of Barnich, Ruth & Haaren, Ton Van, 2021, Revision of Sthenelais Kinberg, 1856, Fimbriosthenelais Pettibone, 1971 and Eusthenelais McIntosh, 1876 (Polychaeta, Sigalionidae) in the Northeast Atlantic, pp. 138-171 in European Journal of Taxonomy 740 on pages 143-145, DOI: 10.5852/ejt.2021.740.1287, http://zenodo.org/record/4649646 : {"references": ["Kinberg J. G. H. 1856. Nya slagten och arter af Annelider. Ofversigt af Kongliga Vetenskaps-Akademiens Forhhandlingar Stockholm 12 (9 - 10): 381 - 388 [read 1855; printed 1856].", "Pettibone M. H. 1971. Partial revision of the genus Sthenelais Kinberg (Polychaeta: Sigalionidae) with diagnoses of two new genera. Smithsonian Contributions to Zoology 109: 1 - 40. https: // doi. org / 10.5479 / si. 00810282.109", "Schmarda L. K. 1861. Neue Turbellarien, Rotatorien und Anneliden beobachtet und gesammelt auf einer Reise um die Erde 1853 bis 1857. Neue Wirbellose Thiere Beobachtet und Gesammelt auf einer Reise um die Erde 1853 bis 1857 1 (2): 1 - 164.", "Wehe T. 2007. Revision of the scale worms (Polychaeta: Aphroditoidea) occurring in the seas surrounding the Arabian Peninsula. Part II. Sigalionidae. Fauna of Arabia 23: 41 - 124.", "Ehlers E. 1864. Die Borstenwurmer (Annelida Chaetopoda) nach systematischen und anatomischen Untersuchungen. 1. Band. Wilhelm Engelmann, Leipzig. https: // doi. org / 10.5962 / bhl. title. 2081", "Johnston G. 1833. Illustrations in British Zoology. Magazine of Natural History and Journal of Zoology, Botany, Mineralogy, Geology and Meterology, London 34: 320 - 324."]}